PEREMPUAN SEBAGAI PUSTAKAWAN: STUDI KASUS DI DISPUSIP KOTA SUNGAI PENUH - Fitri Handayani; Suriyadi Suriyadi; Jalwis Jalwis (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Women are considered as gentle and identical creatures who are very good at providing services. One of the professions that is widely cultivated and in demand by some people is the librarian profession and the profession is mostly carried out by the female gender. The purpose of this research is to find out the role of women as librarians at the Sungai Penuh City Library and Archives Service. The research methodology used is a quantitative descriptive approach to describe the role of women as librarians in the Dispusip of Sungai Penuh City, the data obtained from observations, interviews, documentation and data triangulation, then the results of the interviews are analyzed and linked to theories and concepts related to research. The role of women as librarians in Sungai Penuh City, most of the respondents follow the community's stereotype of working in the library, where they work as librarians related to problems of self, social, and economic existence and the last choice is taken when they want to work not of their own will. This has resulted in the assigned women being often bored and bored in the service department. Meanwhile, regarding the policy on the role of women as librarians in Sungai Penuh City, equal opportunities have been given to women to play a role in the library, although there are still some women as librarians who are not included in the formulation of library program policies.